2020
DOI: 10.3389/fevo.2020.571887
|View full text |Cite
|
Sign up to set email alerts
|

Metacommunity Structures of Macroinvertebrates and Diatoms in High Mountain Streams, Yunnan, China

Abstract: High-Mountain Stream Metacommunity Structuring other. Our study provides substantial elements to further understand metacommunity structure and highlights the necessity of future research to reveal the underlying mechanisms of community structuring in these remote ecosystems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Clementsian structures arise when communities are actually changing consistently through groups of species that respond in a similar way to environmental gradients 23 . These results are consistent with the previous reported that metacommunity structure of diatoms showed Clementsian in river-connected mountain stream 24 . According to the river continuum concept (RCC), the physical properties of the riverine ecosystem were determined by flowing water from upstream to downstream.…”
Section: Discussionsupporting
confidence: 94%
“…Clementsian structures arise when communities are actually changing consistently through groups of species that respond in a similar way to environmental gradients 23 . These results are consistent with the previous reported that metacommunity structure of diatoms showed Clementsian in river-connected mountain stream 24 . According to the river continuum concept (RCC), the physical properties of the riverine ecosystem were determined by flowing water from upstream to downstream.…”
Section: Discussionsupporting
confidence: 94%
“…In many studies, biological methods are valuable for determining natural and anthropogenic influences on water resources and habitats because biota responds to stressors from multiple spatial or temporal scales (Weigel and Robertson, 2007;Resende et al, 2010;He et al, 2020;Kurthen et al, 2020). In addition, the use of aquatic organisms in ecological studies has proven more effective than using environmental variables alone, because the aquatic community integrates structural and functional characteristics and reflects the health of the studied streams (Bonada et al, 2006;He et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We ran a principal components analysis (PCA) for each network separately on our spatial variables of elevation, streamwise distance from headwaters, streamwise distance below upstream lakes, and upstream lake area. Upstream lake area can strongly influence dispersal throughout a river network, as the majority of larval species may not be able to move through large and deep lakes (Bagge, 1995; A. J. Brooks, Wolfenden, et al, 2017; Kurthen et al, 2020; Parisek, 2018). Distance from headwaters, distance below upstream lakes, and elevation all loaded on the first PC axis, which explained 60% of the spatial variation on average for all networks (Evo: 53%, Cascade: 66%, Bubbs: 45%, Rock: 75%) and described a gradient from spatially isolated sites, which were typically found high in the headwaters and close to larger, upstream lakes, to spatially connected sites, which were typically found downstream from the headwaters and downstream from lakes with smaller areas.…”
Section: Methodsmentioning
confidence: 99%